Peran Keluarga dengan Penerapan Asuhan Keperawatan pada Pasien Stroke - Winarsi Pricilya Molintao; Muftadi Muftadi; Wiwie Herdalisa; Adolfina Tandilangan; Jeni Rante Tasik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the role of the family and the application of nursing care to stroke patients. This research method uses a cross-sectional design. The results of this research show that p-value = 0.000 is more minor than α = 0.05. In conclusion, there is a relationship between the role of the family and the implementation of nursing care for stroke patients Keywords: Family Nursing Care, Family, Stroke